Randomized clinical trial of laparoscopic versus open pancreatoduodenectomy for periampullary tumours. Issue 11 (12th September 2017) - Palanivelu, C; Senthilnathan, P; Sabnis, S C; Babu, N S; Srivatsan Gurumurthy, S; Anand Vijai, N; Nalankilli, V P; Praveen Raj, P; Parthasarathy, R; Rajapandian, S
Abstract: Background: Laparoscopic resection as an alternative to open pancreatoduodenectomy may yield short-term benefits, but has not been investigated in a randomized trial. The aim of this study was to compare laparoscopic and open pancreatoduodenectomy for short-term outcomes in a randomized trial. Methods: Patients with periampullary cancers were randomized to either laparoscopic or open pancreatoduodenectomy. The outcomes evaluated were hospital stay (primary outcome), and blood loss, radicality of surgery, duration of operation and complication rate (secondary outcomes). Results: Of 268 patients, 64 who met the eligibility criteria were randomized, 32 to each group. The median duration of postoperative hospital stay was longer for open pancreaticoduodenectomy than for laparoscopy (13 (range 6–30) versus 7 (5–52) days respectively; P = 0·001). Duration of operation was longer in the laparoscopy group. Blood loss was significantly greater in the open group (mean(s.d.) 401(46) versus 250(22) ml; P < 0·001). Number of nodes retrieved and R0 rate were similar in the two groups. There was no difference between the open and laparoscopic groups in delayed gastric emptying (7 of 32 versus 5 of 32), pancreatic fistula (6 of 32 versus 5 of 32) or postpancreatectomy haemorrhage (4 of 32 versus 3 of 32). Overall complications (defined according to the Clavien–Dindo classification) were similar (10 of 32 versus 8 of 32). There was one death in each group. Conclusion: Laparoscopy offered a shorter hospital stay than open pancreatoduodenectomy in this randomized trial. Registration number: NCT02081131(http://www.clinicaltrials.gov ). Abstract : Shorter stay